Disaster risk management at the national level - Mikio Ishiwatari (Asian Development Bank Institute (ADBI), 2013)
National governments are supposed to play a pivotal role in disaster risk management (DRM). This paper reviews trends and patterns in developing governance and institutions in DRM in the Asia and the Pacific region. The paper then derives recommendations on how to establish disaster risk governance for developing countries, including mainstreaming DRM into development plans and policies. A four-pronged approach is presented: First, strengthen the DRM coordination role of the national government. Second, develop an enhanced legal framework. Third, establish a DRM focal point agency. Fourth, build a flexible cooperation system among concerned organizations and all levels of government.
Keywords: Q54; H84; 330; disaster risk management; asia; pacific; disaster risk governance